Comparative bioacoustical studies on flight and buzzing of neotropical bees - Burkart, Andreas; Lunau, Klaus; Schlindwein, Clemens (Journal of Pollination Ecology, 2012)
The presence of bees is typically accompanied by the humming sound of their flight. Bees of several tribes are also capable of pollen collecting by vibration, known as buzzing behaviour, which produces a buzzing sound, different from the flight sound. An open question is whether bee species have species-specific buzzing patterns or frequencies dependent of the bees' morphology or are capable to adjust their indivudual buzzing sound to optimize pollen return. The investigations to approach this issue were performed in northeastern Brazil near Recife in the state of Pernambuco. We present a new field method using a commercially available portable system able to record the sound of bees during flight and buzzing at flowers. Further, we describe computer linguistical algorithms to analyse the frequency of the recorded sound sequences. With this method, we recorded the flight and buzzing sequences of 59 individual bees out of 12 species visiting the flowers of Solanum stramoniifolium and S. paniculatum. Our findings demonstrate a typical frequency range for the sounds produced by the bees of a species. Our statistical analysis shows a strong correlation of bee size and flight frequency and demonstrate that bee species use different frequency patterns.